MANAGEMENT STRATEGIES FOR THE DEVELOPMENT OF MICRO ENTERPRISES IN NORTH BENGKULU DISTRICT - Anjari Wahyu Wardhani; Liu Zeqing; Zhang Zhiquan; Ridwan Nurazi; Berto Usman (PT. Altin Riset Publishing, 2025)
The objective of this community service program (PKM) is to analyze management strategies for the development of micro-entrepreneurs in North Bengkulu Regency, with a focus on the promotion of QRIS (Quick Response Code Indonesian Standard) usage and the provision of Medium Business Credit (KUM) by Bank Bengkulu to support the growth of micro, small, and medium enterprises (MSMEs) in the region. The research employs lecture methods, interactive discussions, and simulation techniques to obtain a comprehensive understanding of business profiles, challenges faced, and the financial needs of MSMEs. The QRIS outreach initiative is conducted through various media and hands-on training sessions aimed at improving digital literacy and promoting the adoption of digital payment technologies among entrepreneurs. Additionally, management strategies are implemented to assist MSMEs in accessing Medium Business Credit provided by Bank Bengkulu. These strategies include business plan development, technical assistance, and financial management training. The results indicate that the use of QRIS enhances transaction efficiency and market access for MSMEs. Meanwhile, access to Medium Business Credit enables entrepreneurs to secure the capital needed for business expansion and increased production capacity. Strategic training and managerial assistance have proven effective in improving business management capabilities, which in turn enhance business performance and sustainability. Recommendations include expanding QRIS outreach programs, tailoring credit products to better suit MSME needs, and providing continuous management support to ensure stable and sustainable growth for MSMEs in North Bengkulu District.